2022
DOI: 10.1111/jan.15317
|View full text |Cite
|
Sign up to set email alerts
|

‘I knew I'd be taken care of’: Exploring patient experiences in the Emergency Department

Abstract: Aims: To explore adult Emergency Department patient experiences to inform the development of a new Emergency Department patient-reported experience measure. Design: Descriptive, exploratory qualitative study using semi-structured individual interviews with adult Emergency Department patients. Methodology: Participants were recruited across two Emergency Departments in Southeast Queensland, Australia during September and October 2020. Purposive sampling based on maximum variation was used. Participants were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…This is also recognised in the literature, for example in a prospective observational study of pain management in the ED by Van Zanden and colleagues [43] where 43.7% of patients arriving in the ED desired pain relief, and the provision of pain relief was associated with higher satisfaction. Pain was also highlighted in a recent qualitative study exploring patients' experiences in an Australian ED [40]. Many patients in this study described pain as a memorable aspect of their ED visit.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This is also recognised in the literature, for example in a prospective observational study of pain management in the ED by Van Zanden and colleagues [43] where 43.7% of patients arriving in the ED desired pain relief, and the provision of pain relief was associated with higher satisfaction. Pain was also highlighted in a recent qualitative study exploring patients' experiences in an Australian ED [40]. Many patients in this study described pain as a memorable aspect of their ED visit.…”
Section: Discussionmentioning
confidence: 73%
“…Patients in our study have provided narratives that will contribute to the further development of PREM-ED 65. This study builds on the body of the existing literature emphasising patients' desire to have their basic human needs and comfort addressed during emergency care episodes [25,39,40]. If aiming to optimise patient experience, the provision of humanistic, holistic care should be considered an important caring aspect of the ED alongside the clinical objectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the choice away leads to a worse care experience and may increase the risk that they will not return to care when needed [ 27 ]. Research has shown that sharing information about care and involving vulnerably housed patients in treatment decision-making alleviated anxiety, fear, and feelings of isolation in the ED, and demonstrated to patients that healthcare providers are tailoring plans to their individual needs [ 28 ]. One study demonstrated that vulnerably housed patients welcome questions from ED healthcare providers related to housing status and resources [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study participants felt that frequent touchpoints from healthcare providers during the visit would significantly improve the experience. Patients also feel ignored, insecure, and frustrated at long wait times [ 28 ]. Frequently they may assume that nothing is being done for them during those times because of bias related to their homeless status.…”
Section: Discussionmentioning
confidence: 99%